برنامج لإدارة سجلات الموظفين والحضور والإجازات - ميسة, شفاء; حوري, وئام فرح; بية, حنيــن (Université of Eloued جامعة الوادي, 2026)
يتناول هذا المشروع تطوير نظام إدارة سجلات الموظفين والحضور والإجازات باستخدام نمذجة UML والتجسيد البرمجي لضمان كفاءة التشغيل وسهولة الاستخدام. لتجسيد هذا المشروع تم الاعتماد على النمذجة في تصميم الأنظمة البرمجية ودورها في تحسين فهم النظام وتوثيقه عبر مخططات تحليلية دقيقة، حيث اعتمدنا في مرحلة التنفيذ على HTML، CSS، JavaScript، وPHP لإنشاء واجهات النظام، مع استخدام MySQL لإدارة قاعدة البيانات وضمان سرعة الوصول إلى المعلومات، بالإضافة إلى تشغيل النظام عبر XAMPP كبيئة تطوير محلية. يكتسي هذا المشروع أهمية كبيرة لأنه يناول تكامل النمذجة والتجسيد في تحسين أداء النظام الإداري. يعكس هذا المشروع أهمية الاستفادة من التكنولوجيا الحديثة في تطوير الأنظمة الإدارية، حيث يساهم الدمج بين التصميم المسبق والتنفيذ الفعلي في تحقيق التحول الرقمي ورفع كفاءة المؤسسات. This project focuses on the development of an employee records, attendance, and leave management system using UML modeling and software implementation to ensure operational efficiency and ease of use. To realize this project, we relied on modeling for system design and its role in improving understanding and documentation through precise analytical diagrams. During the implementation phase, we used HTML, CSS, JavaScript, and PHP to create the system interfaces, with MySQL used to manage the database and ensure fast access to information. Additionally, the system was run using XAMPP as a local development environment. This project holds significant importance as it addresses the integration of modeling and implementation to improve the performance of administrative systems. It highlights the importance of leveraging modern technology in administrative system development, where the combination of prior design and actual implementation contributes to digital transformation and enhances institutional efficiency.
مذكرة تخرج ليسانس اعلام آلي
Keywords: l’efficacité opérationnelle.la base de données.; كفاءة التشغيل.قاعدة البيانات.